Prevalent North Atlantic Deep Water during the Last Glacial Maximum and Heinrich Stadial 1. ... - Blaser, Patrick; Waelbroeck, Claire; Thornalley, David J R; Lippold, Jörg; Pöppelmeier, Frerk; Kaboth-Bahr, Stefanie; Repschläger, Janne; Jaccard, Samuel L (University of Bern, 2025)
Deep ocean circulation modulated glacial-interglacial climates through feedbacks to the carbon cycle and energy distribution. Past work has suggested that contraction of well-ventilated North Atlantic Deep Water during glacial times facilitated carbon storage in the deep ocean and drawdown of atmospheric CO2 levels. However, the spatial extent and properties of different water masses remain uncertain, in part due to conflicting palaeoceanographic proxy reconstructions. Here we combine five independent proxies to increase confidence and reconstruct Atlantic deep water distributions during the Last Glacial Maximum (around 21 thousand years ago) and the following Heinrich Stadial 1-a time when massive ice rafting in the North Atlantic interfered with deep water formation and caused global climate shifts. We find that North Atlantic Deep Water remained widespread in both periods, although its properties shifted from a cold, well-ventilated mode to a less-ventilated, possibly warmer, mode. This finding implies a ...